Computer-animated stimuli to measure motion sensitivity: constraints on signal design in the Jacky dragon - Woo, Kevin L. (Curr Zool, 2017)
Identifying perceptual thresholds is critical for understanding the mechanisms that underlie signal evolution. Using computer-animated stimuli, we examined visual speed sensitivity in the Jacky dragon Amphibolurus muricatus, a species that makes extensive use of rapid motor patterns in social communication. First, focal lizards were tested in discrimination trials using random-dot kinematograms displaying combinations of speed, coherence, and direction. Second, we measured subject lizards’ ability to predict the appearance of a secondary reinforcer (1 of 3 different computer-generated animations of invertebrates: cricket, spider, and mite) based on the direction of movement of a field of drifting dots by following a set of behavioural responses (e.g., orienting response, latency to respond) to our virtual stimuli. We found an effect of both speed and coherence, as well as an interaction between these 2 factors on the perception of moving stimuli. Overall, our results showed that Jacky dragons have acute sensitivity to high speeds. We then employed an optic flow analysis to match the performance to ecologically relevant motion. Our results suggest that the Jacky dragon visual system may have been shaped to detect fast motion. This pre-existing sensitivity may have constrained the evolution of conspecific displays. In contrast, Jacky dragons may have difficulty in detecting the movement of ambush predators, such as snakes and of some invertebrate prey. Our study also demonstrates the potential of the computer-animated stimuli technique for conducting nonintrusive tests to explore motion range and sensitivity in a visually mediated species.